Assistance for Micro Business Owned by Alumni: Campus Supports Alumni - Marthen Luther Sowe; Marsi Adi Purwadi (Universitas Brawijaya, 2022)
This service activity aims to 1) identify the characteristics of micro-businesses owned by Graduate Students (Alumni) of the Faculty of Economics and Business; 2) Examine the micro-business opportunities and challenges in accordance with the business needs of the alumni of the Faculty of Economics and Business. The results showed that only a small number of alumni of the Faculty of Economics and Business choose to become entrepreneurs. Besides, the alumni of the Faculty of Economics and Business faced challenges during the Covid-19 pandemic affecting sales turnover due to the Public Activity Restriction Policy (PPKM) which limits community activities above 20.00 Eastern Indonesian Time (WIT). However, on average, the businesses were open at 17.00 Eastern Indonesian Time (WIT) or only 3 hours before the restriction time. Indeed, there was assistance based on the main needs of businesses to help ease the production burden. The assistance was in the form of providing raw materials for the Angkringan Wayae business and coffee brewing equipment for Zamo Caffee business.